Forgotten double J stent in crossed renal fused ectopia: a rare case report - Kumar, Prashant; Joseph, Sachin; Misra, Pabitra Kumar; Nair, Kiran S. (International Surgery Journal, 2020)
Ureteral double J (DJ) sent has now become one of the most commonly used tools in endourology. Complications are bound to occur if forgotten to remove, such as encrustations, infection, migration, renal dysfunction, hydronephrosis. Crossed renal fused ectopia is a very rare congenital malformation due to abnormal kidney ascent with fusion during embryogenesis in the first trimester. we report a very rare case of forgotten DJ stent in crossed fused ectopia, in 66 years old diabetic patient post left ureterorenoscopy (URS) done 3 years back. Retrograde intrarenal surgery (RIRS) was done for DJ stent removal right.